Evaluation of a new point-of-care test to determine prior dengue infection for potential use in pre-vaccination screening. (June 2021) - Daag, Jedas Veronica; Ylade, Michelle; Adams, Cameron; Jadi, Ramesh; Crisostomo, Maria Vinna; Alpay, Riacarl; Aportadera, Emma Teresa Carmela; Yoon, In-Kyu; White, Laura; Deen, Jacqueline; de Silva, Aravinda M.; Lopez, Anna Lena
Abstract: Objective: Vaccination with the first licensed dengue vaccine is recommended only for those who have had previous infection with dengue virus (DENV). A point-of-care test with the desired sensitivity of 95% and specificity of 98% could facilitate pre-vaccination screening. We evaluated a newly developed, automated dengue immunoglobulin fluorescence immunoassay for determining dengue serostatus. Methods: We used serum samples collected just prior to a mass dengue vaccination in Cebu, Philippines. Healthy children residing in Bogo and Balamban who would be 9–14 years old at the time of the mass dengue vaccination were eligible to participate. We evaluated the ichroma™ II dengue fluorescence immunoassay (Boditech Med Incorporated, Gang-won-do, Republic of Korea) using a neutralization test (NT) as the reference assay. Results: We enrolled 2996 children (mean age 10.39 years, 51.7% female) in the cohort and included a subsample of 1000 (mean age 10.56 years, 54.4% female) in this study. Of the 1000 children, 86/1000 (8.6%) tested seronegative and 914/1000 (91.4%) seropositive for DENV antibodies by neutralization testing. Compared with the NT, the dengue IgG fluorescence immunoassay had an overall specificity of 90.7% (95%CI: 82.5–95.9%) and a sensitivity of 91.8% (95%CI: 89.8–93.5%) for determining dengue seropositivity. The sensitivity declined to 51.2% (42.3–61.0%) for the detection of the subset with a monotypic dengue profile. Conclusion: The insufficient specificity and sensitivity (particularly in the detection of a previous monotypic dengue infection) would render the test, in its current state, inadequate for pre-vaccination screening. Considering its user-friendly interphase and possibility of point-of-care use, the test could be further developed and validated to improve its performance characteristics.